(untitled) (XXI Century. Spanish Literature and Culture, 2005)
The work begins with a general summary of theater shows produced in Spain during 2004, with surprising numbers, but that need to be explained. It also deals with the year’s most important openings, examining both classical and modern-day productions, in addition to adaptations of works by foreign authors.